2022
DOI: 10.3390/agronomy12020460
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Multivariate Correction Method for HVI Fibrogram Measurements

Abstract: Cotton fiber length parameters are used across the cotton industry to select elite germplasm, purchase cotton bales and manage mill throughput. The High Volume Instrument (HVI) provides the most commonly used fiber length parameters, upper half mean length (UHML) and uniformity index (UI). UI is the ratio of mean length (ML) to the UHML expressed as a percentage. These length parameters, UHML and ML, are generated following the fibrograph principle and are highly correlated with two span lengths on the fibrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It was apparent that almost all samples had a lower bias rate using the proposed theoretical reflectance than that adopting the ideal and original reflectance, except for 10# and 18#, with a slightly larger difference of 0.04% and 0.13% than the ideal R 1 . Hence, this method was demonstrated to be effective, and red light was employed in the following study for higher light penetration than the others just as that of the HVI 18,19 and AFIS. 20,22…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was apparent that almost all samples had a lower bias rate using the proposed theoretical reflectance than that adopting the ideal and original reflectance, except for 10# and 18#, with a slightly larger difference of 0.04% and 0.13% than the ideal R 1 . Hence, this method was demonstrated to be effective, and red light was employed in the following study for higher light penetration than the others just as that of the HVI 18,19 and AFIS. 20,22…”
Section: Resultsmentioning
confidence: 99%
“…15 However, HVI cannot provide efficient data for colored cotton and short fiber content because of ignoring material reflectance and scattering in the L–B law. 1619 In comparison, the AFIS system uses infrared light to measure at least 3000 single fibers, straightened by airflow. 3,20,21 Although its principle was unclear, 22,23 it was proved to have high consistency with HVI using the beard for raw cotton.…”
mentioning
confidence: 99%
“…In 2021, Sayeed et al demonstrated that the whole fibrogram curve captures additional fiber length information than what is provided by the current HVI length parameters [24]. Later, they developed a method to calibrate the whole fibrogram and showed that the whole fibrogram could be calibrated to bring the measurement to a similar level across multiple HVIs [33]. Addisu et al showed that several span lengths can be calibrated to compare the fibrogram measurements across multiple HVIs [34].…”
Section: Introductionmentioning
confidence: 99%
“…Using the complete fibrogram curve, they used principal component analysis to extract three independent variables from the fibrogram to represent the variation captured by the entire curve and showed that these three variables predict yarn quality better than the current HVI length parameters. Later, Sayeed et al 15 developed a multivariate correction method to align the fibrogram measurement as a whole curve across multiple HVIs and demonstrated that it is possible to bring the fibrogram measurements at a similar level across many HVIs. Also, Tesema et al 16 showed that the whole fibrogram curve is stable and repeatable over long-and shortterm periods for a single HVI by examining several span lengths along the curve.…”
mentioning
confidence: 99%
“…Later, Sayeed et al. 15 developed a multivariate correction method to align the fibrogram measurement as a whole curve across multiple HVIs and demonstrated that it is possible to bring the fibrogram measurements at a similar level across many HVIs. Also, Tesema et al.…”
mentioning
confidence: 99%